2011
DOI: 10.1016/j.ecosys.2011.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Foreign and domestic growth drivers in Eastern Europe

Abstract: This paper analyses the growth effects of capital formation, exports and FDI as major drivers of economic development in Eastern Europe. The fundamental innovations are identified by empirically and theoretically motivated short-and long-run restrictions in structural cointegrated vector autoregressions. Impulse responses and variance decompositions reveal quite different growth effects in various Eastern European countries. Generally, strong reliance on exports goes along with higher GDP, and FDI bears substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Andonova (2003) results indicated that although export-oriented businesses adopt green technologies more quickly, this is not always a result of foreign investment. Higher GDP is correlated with a greater reliance on exports, and FDI has a signi cant potential to promote economic growth (Enzo, 2011). However, the between transformation output is in Table 7.…”
Section: Regression Resultsmentioning
confidence: 99%
“…Andonova (2003) results indicated that although export-oriented businesses adopt green technologies more quickly, this is not always a result of foreign investment. Higher GDP is correlated with a greater reliance on exports, and FDI has a signi cant potential to promote economic growth (Enzo, 2011). However, the between transformation output is in Table 7.…”
Section: Regression Resultsmentioning
confidence: 99%